The immune responses to bacterial antigens encountered in vivo at mucosal surfaces. - Dougan, G; Ghaem-Maghami, M; Pickard, D; Frankel, G; Douce, G; Clare, S; Dunstan, S; Simmons, C (2000)
Mammals have evolved a sophisticated immune system for handling antigens encountered at their mucosal surfaces. The way in which mucosally delivered antigens are handled influences our ability to design effective mucosal vaccines. Live attenuated derivatives of pathogens are one route towards the development of mucosal vaccines. However, some molecules, described as mucosal immunogens, are inherently immunogenic at mucosal surfaces. Studies on mucosal immunogens may facilitate the identification of common characteristics that contribute to mucosal immunogenicity and aid the development of novel, non-living mucosal vaccines and immunostimulators.